Pelatihan AI Untuk Literasi Digital Dan Ekonomi Desa Sidolego, Kecamatan Tabir Lintas, Kabupaten Merangin, Jambi - Setiadi, Arif; Saputra, Abe Wisnu; Ariantoro, Tri Rizqi; Husni, Akhmad Faisal; Siagian, Saut; Handini, Nurul Sri (Jurnal Pengabdian Masyarakat, 2024)
Sidolego Village, Tabir Lintas District, Merangin Regency has great potential for natural and human resources, but has not been optimally utilized due to limited digital knowledge and skills. This digitalization training aims to improve digital literacy in village communities and encourage village economic growth through the use of artificial intelligence (AI) technology. This training will cover basic digital materials, the use of AI for various village economic sectors (agriculture, animal husbandry, crafts, and so on), as well as digital marketing strategies. The training method used is a combination of lectures, discussions, case studies, and direct practice. The results obtained from this training are an increase in the understanding of village communities about digital technology and AI, as well as their ability to apply it to increase productivity and income. Of the 40 participants, 85% of participants showed an increase in understanding of the basic concepts of AI, information search 90% of participants were able to use AI to search for information effectively, content creation 75% of participants were able to create simple content with the help of AI and online communication 95% of participants felt more confident in communicating online after participating in the training. Ultimately, this training is expected to contribute to the realization of independent and competitive digital villages.